Fatty acids profile in Awassi sheep milk affected by some genes’ single and combined effects. - Jawasreh, Khaleel I; Khrais, Dana; Alu’dat, Muhammad; Haddad, Nizar J; Awabdeh, Sami; Al Madani, Mohammad Isam; Brake, Mohamad; Al Araishi, Mohamad Ahmad; Sadder, Monther; Al Amareen, Ahmad (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study intended to figure out the effects of fixed effects and genes such as beta-lactoglobulin (β-LG), prolactin (PRL), annexin A9 (ANXA9), and acetyl-CoA acyltransferase 2 (ACAA2) on the structure of fatty milk acids in Awassi ewes, as well as any potential genotype-genotype interactions. Materials and Methods: Fatty acid (FA) profile and other milk components were examined from 116 Awassi ewes in total. Polymerase chain reaction (PCR) was used to extract and genotype their DNA, and either sequencing or restriction fragment length polymorphism (RFLP) analysis came next. Results: Saturated, medium-chain, and long-chain FA proportions were not significantly impacted by the genotypes of β-LG, PRL, ANXA9, and ACAA2. Conversely, ewes with the β-LG AA genotype displayed higher levels of monounsaturated fatty acids (MUFAs), while the β-LG AB genotype was linked to the highest levels of polyunsaturated fatty acids (PUFAs). It has been demonstrated that PUFA levels are impacted by single nucleotide polymorphisms (SNPs) of ANXA9, while VLCFA and PUFA levels are changed by SNPs of ACAA2. The PRL AA genotype showed the greatest influence on VLCFA. Furthermore, milk exhibited the highest levels of MUFA and PUFA due to the interaction between β-LG and PRL. The interaction PRL-ANXA9 exhibited the greatest levels of VLCFA. Additionally, Dam lambing weight affected the levels of MUFA, MCFA, and long-chain fatty acids. Conclusion: To increase the levels of MUFA and PUFA constituents, the selection program should effectively harness and integrate the synergistic benefits of β-LG, PRL, ANXA9, and ACAA2 as well as their interaction. J. Adv. Vet. Anim. Res., 12(1): 238–251, March 2025 http://doi.org/10.5455/javar.2025.l891